A comparison of the clinical outcomes of induced and spontaneous labour in patients with gestational diabetes - Ofelia A. Bettikher; Irina E. Zazerskaya; Polina V. Popova; Vitaliy N. Kustarov (Сахарный диабет)
Aim. To evaluate the clinical outcomes of induced and spontaneous labour in patients with gestational diabetes (GD).Materials and methods. This retrospective cohort study conducted at the Federal Almazov Northwest Medical Research Centre included 251 patients with GD who had given birth during 2014. The patients were divided into the following two groups: one included 210 patients who were treated with diet and the other included 41 patients who were treated with insulin. Clinical outcomes were compared between patients who had induced (n = 43) or spontaneous (n = 188) labour.Results. Complications of labour, such as dysthyroidism and uterine inertia, were significantly more common (p < 0. 05) in induced labour patients than in those who had spontaneous labour (16. 3 vs. 3. 2% and 7% vs. 0%, respectively). Fetal distress occurred in 10. 6% and 9. 3% of patients during spontaneous and induced labour, respectively. The frequency of ceasarean section after induced labour was not significantly greater than that among patients who had spontaneous labour.Conclusion. Delivery at 38 to 39 weeks in women with GD has led to an increase in the rate of birth complications, such as uterine inertia and dysthyroidism. Gestational age cannot be considered as a sufficient indicator of labour induction at full-term in the absence of foetus distress or poor maternal glycemic control.